Lifetime Spectroscopy A Method of Defect Characterization in Silicon for Photovoltaic Applications - Rein, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Lifetime spectroscopy is one of the most sensitive diagnostic tools for the identification and analysis of impurities in semiconductors. Since it is based on the recombination process, it provides insight into precisely those defects that are relevant to semiconductor devices such as solar cells. This book introduces a transparent modeling procedure that allows a detailed theoretical evaluation of the spectroscopic potential of the different lifetime spectroscopic techniques. The various theoretical predictions are verified experimentally with the context of a comprehensive study on different metal impurities. The quality and consistency of the spectroscopic results, as explained here, confirms the excellent performance of lifetime spectroscopy.
Theory of carrier lifetime in silicon -- Lifetime measurement techniques -- Theory of lifetime spectroscopy -- Defect characterization on intentionally metal-contaminated silicon samples -- The metastable defect in boron-doped Czochralski silicon -- Summary and further work -- Zusammenfassung und Ausblick.
Keywords: Physics; Solid state physics; Spectroscopy; Microscopy; Optical materials; Electronic materials; Physics; Solid State Physics; Spectroscopy and Microscopy; Optical and Electronic Materials; Electronic books